Breeding-site fidelity and colony formation in the Great Black-headed Gull - Kharitonov, S.P. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 1999)
The main study was carried out in April-early May of 1989-1982 at the Koyanly Islands (45.56 N, 34.56 E), the Eastern Sivash, the Sea of Azov, the Southern Ukraine. Some data collected in 1995 and 1999 at Koyanly Islands, Chongar and Kitay Islands were also involved. The total number of breeding Great Black-headed Gulls in 1989 on Koyanly Islands comprised 197 pair (5 colonies, from 4 to 11 nest), in 1990-238 pairs (2 colonies, 207 and 31 pairs). In 1991 Koyanly Islands held a single colony of 50 nests+ one single nest. The colony on Chongar Islands in 1991 contained about 200 nests. In 1992 Koyanly Island held a single colony of 65 nests, Chongar – about 175 nests. In 1995 a colony at Koyanly Islands contained 22 nests, Chongar – 45 nests, Kitay Island – 300 nests. In 1999 the only colony of 420 nests was found at Kitay Island. In 1989 and 1990, fifty-eight adult birds were caught on their nests using alfa-chloralose. All of them were tagged. They gave a total of 461 field sightings. In the length of the four seasons 22 gulls were recorded during 2 successive seasons, 12 gulls during 3 seasons, 1 gull was noticed in all 4 seasons.